NEUROLEPTIC MALIGNANT SYNDROME: A SIXTEEN YEARS RETROSPECTIVE REVIEW - Faizi, Abul; Naqvi, Haider A. (Journal of Pakistan Psychiatric Society, 2007)
Objective: To study demographic characteristics, psychiatric diagnosis, type of neuroleptic drugs administered, course of illness, management and outcome.Design: Retrospective chart review study.Place and duration of study: This study was carried out for sixteen years (1988-2004) in the Psychiatryunit, Aga Khan University Hospital, Karachi.Subjects and Methods: Sample consisted of 25 cases of Neuroleptic Malignant Syndrome in which 13were males and 12 were females. The record was taken from the health information management systemwhich keeps a comprehensive chart of each patient. This renders the files retrievable through computergenerated search. A specific data collection form was designed for extraction of relevant data. The datawas analyzed using SPSS version 13.0.Results: Twenty five cases were identified, of which thirteen were males. Mean age was 45 years (range20-74 years). Bipolar affective disorder was the most common diagnosis followed by schizo-affectivedisorder, schizophrenia, postpartum psychosis, dementia and Parkinsonism. 48% of the patients hadprevious history of neuroleptic use, while 28% received neuroleptics for the first time. Among neurolepticusers, 20% were on long-acting depot antipsychotics. 52% received per-oral dose (PO), while 32% received intramuscular (IM) dose. 56% patients were on other concomitant medications among which Lithiumwas the most common (16%). 96% patients had the cardinal symptoms of fever, rigidity and increasedcreatine phosphokinase (CPK). 96% had associated delirium, 80% showed autonomic instability withfluctuation in pulse and blood pressure. Electrolyte disturbance was seen in 84% and diaphoresis withleukocytosis was present in 68% patients. NMS was associated with high ambient temperature with meantemperature of 39.20C (S.E. 0.3). Discontinuation of neurolpetic medications and supportive care wascarried out in all cases. In our case series we observed mortality rate of 16%. Out of 25 patients, 21recovered with early diagnosis and adequate management.Conclusion: Risk of NMS can be minimized by use of low potency or atypical antipsychotics, cautioususe of concomitant medications and depot preparations and initiation of neurolpetics at lower dose withcareful monitoring. With good supportive medical care mortality can be substantially mimimized.Key words: Neuroleptic malignant syndrome (NMS), neuroleptics, creatine phosphokinase (CPK).